Welding considerations for duplex steel sluice gates in water pipelines - Gabriel Gârleanu; Delia Gârleanu; Marinela Marinescu; Larisa Butu; Claudia Borda (Journal of Research and Innovation for Sustainable Society)
The article presents the finding of an optimal technology for welding an oversized construction, from an LDX 2101 duplex steel. The biggest problems are related to the occurrence of stresses and deformations after welding. Also, depending on the parameters of the welding regime, the structure of the material, and the amount of ferrite/austenite can also be modified. These changes will also lead to changes in mechanical properties and corrosion resistance. The article also presents the problems that can arise from the inadequate choice of the filler material, cracks in the weld seam, for a heterogeneous joint, and how to make the optimal choice.